Analgesic efficacy of ultrasound guided quadratus lumborum block versus ilioinguinal/iliohypogastric nerve block following pediatric open inguinal hernia repair: A prospective randomized controlled trial - Shaimaa F Mostafa; Mohamed S Abdelghany; Mohamed M Abu Elyazed (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Inguinal hernia repair is a common surgical procedure. We compared the analgesic efficacy of ultrasound-guided anterior quadratus lumborum (QL) block versus ilioinguinal/iliohypogastric (II/IH) nerve block in pediatric patients undergoing open inguinal hernia repair. Material and Methods: It was a prospective randomized study in which 90 patients of 1-8 years of age were randomly assigned into control (general anesthesia only), QL block, and II/IH nerve block groups. Children's Hospital Eastern Ontario Pain Scale (CHEOPS), perioperative analgesic consumptions, and time to first analgesic request were recorded. The normally distributed quantitative parameters were analyzed by one-way ANOVA with post-hoc Tukey's HSD test while parameters that did not follow a normal distribution and the CHEOPS score were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney U test with Bonferonni correction for post-hoc analysis. Results: In the 1st 6h postoperative, the median (IQR) CHEOPS score was higher in the control group than II/IH group (P = 0.000) and QL group (P = 0.000) while comparable between the latter two groups. CHEOPS scores were significantly lower in the QL block group than the control group and II/IH nerve block group at 12 and 18h. The intraoperative fentanyl and postoperative paracetamol consumptions in the control group were higher than II/IH and QL groups while lower in QL than II/IH group. Conclusion: Ultrasound-guided QL and II/IH nerve blocks provided effective postoperative analgesia in pediatric patients undergoing inguinal hernia repair with lower pain scores and less perioperative analgesic consumptions in the QL block group compared to II/IH group.